Effect Of Vanillin On Cell Viability, Morphological Characteristics, Apoptosis And Mitochondrial Potential Of Human Oral Cancer Cell Line Kb: An In-Vitro Study - Insha Naseer; Chakkaravarthy Elanchezhiyan; Khursheed Ahmad Dar; Towseef Hassan (International Journal of Psychosocial Rehabilitation, 2020)
Vanillin is utilized as a flavour ingredient in food, fragrance and pharmaceutical sectors.. It has been linked to a varietyof biological effects and has shown antioxidant, antimicrobial, analgesic, anti-sickling, anti-carcinogenic and anti-mutagenic properties in a variety of in vitro models. This research investigated the anticancer potential of vanillin against KB, ahuman oral cancer cell line. Cell viability assays, acridine orange (AO)-ethidium bromide (EB) double staining, as well as other assays being used, intracellular reactive oxygen species level by using dichloro-dihydro-fluoresceindiacetate (DCFH-DA) assay and the laser dye Rh-123 mitochondrial potential (MMP) assay. Vanillin also has higher cytolytic or cytostatic effect on malignant KB cells than on normal cells. With increase in concentration of drug, the cell viability decreased. The IC50 for KB cell lines were 400 μg/ml. Results showed that apoptosis wasinduced by vanillin. Disturbance and loss of mitochondrial potential was detected by green fluorescence imaging ascompared to control for vanillin treatments. In our study, intracellular ROS generation was increased in KB cells. In conclusion vanillin could be a helpful oral cancer preventing agent.